Analisis Sikap Keagamaan Tokoh Utama dalam Novel "Rentang Kisah" Karya Gita Savitri Devi - Sugiarti; Nur Hanifa (Edukasi Lingua Sastra, 2022)
Religious attitudes became essential to the main character because it was an indication of a servant's obedience to his Lord. The study is intended to describe (1) forms of religious attitude of the lead character in the novel Rentang Kisah by Gita Savitri Devi and (2) factors that influenced the religious attitude of the lead character in the novel Rentang Kisah by Gita Savitri Devi. The approach used in this study is religious psychology. The research data source is Gita Savitri Devi's Rentang Kisah novel. Research data consists of a storyline of words, sentences, and paragraphs that are relevant to the focus of the study. Data collection is done using the listen and take notes. Data analysis is made by identifying data, classifying data, analyzing data, and drawing conclusions. Research shows that (1) forms of religious attitude lead character in Gita Savitri Devi's Rentang Kisah novel include belief in the traditional, belief in religious consciousness, and inaction. (2) factors that affect religious attitudes of internal and external factors. The conclusion of the religious attitude of the lead character in the novel Rentang Kisah by Gita Savitri Devi’s is that religious attitude are shaped by the consciousness of the Gita character influenced by family, friendship, and environment.